2020
DOI: 10.3390/sci2040083
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Temperature and CO2: Hen-Or-Egg Causality?

Abstract: It is common knowledge that increasing CO2 concentration plays a major role in enhancement of the greenhouse effect and contributes to global warming. The purpose of this study is to complement the conventional and established theory, that increased CO2 concentration due to human emissions causes an increase in temperature, by considering the reverse causality. Since increased temperature causes an increase in CO2 concentration, the relationship of atmospheric CO2 and temperature may qualify as belonging to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 78 publications
2
40
0
Order By: Relevance
“…As it turns out, considering this less contentious CO 2 series does not resolve the apparently counterintuitive finding that GMTA explains a larger portion of the forecast error variance of CO 2 than vice versa. Such a finding has also been reported using a different methodology in Koutsoyiannis and Kundzewicz (2020). We explore a last avenue, that of using annual CO 2 emissions rather than RF CO 2 t .…”
Section: What's Up With Co 2 ?supporting
confidence: 60%
“…As it turns out, considering this less contentious CO 2 series does not resolve the apparently counterintuitive finding that GMTA explains a larger portion of the forecast error variance of CO 2 than vice versa. Such a finding has also been reported using a different methodology in Koutsoyiannis and Kundzewicz (2020). We explore a last avenue, that of using annual CO 2 emissions rather than RF CO 2 t .…”
Section: What's Up With Co 2 ?supporting
confidence: 60%
“…According to Kuhn et al [47], four billion years ago the solar irradiance was about 80% of the current value (or, according to other estimates, 75%), the Earth's rotation rate was 170% of the current, the land area was very small, less than 4% of the current value, and the atmospheric CO 2 concentration was about three orders of magnitude higher or more (up to 250,000%; see this information in a combined graph in [48]). Note that even in the Cenozoic (the last 65 million years) the atmospheric CO 2 concentration varied by more than two orders of magnitude (see graph in [49]). Amazingly however, despite these cosmogonic changes, the temperature remained fairly constant (varying by only 10%, which is equivalent to 29 K) during all these four billion years.…”
Section: Climate and Watermentioning
confidence: 99%
“…The importance of the effect of the different greenhouse gases, or other agents affecting climate, is not necessarily related to the research efforts and scientific publications on each of them. Arguably, the fact that the CO 2 has been so heavily and repeatedly studied, particularly in paleoclimatology studies (e.g., [49,[51][52][53][54][55][56][57]), does not suggest that it is more important a greenhouse gas than water. A simpler explanation is that CO 2 concentration is easier to study because its change in time is smoother, because its spatial heterogeneity is much lower than that of water vapour, and because it can be detected in ice and sediment cores, stomatal complexes, etc.…”
Section: Climate and Watermentioning
confidence: 99%
See 1 more Smart Citation
“…To this natural process we should add the fact that the increase of temperature (T) results in increased respiration of the biosphere on land and sea. Based on such considerations and using reliable instrumental measurements of global T and CO2 concentration, covering the time interval 1980-2019, a recent study [50] has found that, in the relationship of CO2 and temperature, the dominant causality direction is T → CO2, rather than the other way round, despite the latter being the common perception.…”
mentioning
confidence: 99%